Characterization of the Interaction between the Nuclease and Reverse Transcriptase Activity of the Yeast Telomerase Complex - Niu, Hongwu (American Society for Microbiology, 2000)
Telomerase is a ribonucleoprotein that mediates extension of the dG-rich strand of telomeres in most eukaryotes. Like telomerase derived from ciliated protozoa, yeast telomerase is found to possess a tightly associated endonuclease activity that copurifies with the polymerization activity over different affinity-chromatographic steps. As is the case for ciliate telomerase, primers containing sequences that are not complementary to the RNA template can be efficiently cleaved by the yeast enzyme. More interestingly, we found that for the yeast enzyme, cleavage site selection is not stringent, since blocking cleavage at one site by the introduction of a nonhydrolyzable linkage can lead to the utilization of other sites. In addition, the reverse transcriptase activity of yeast telomerase can extend either the 5′- or 3′-end fragment following cleavage. Two general models that are consistent with the biochemical properties of the enzyme are presented: one model postulates two distinct active sites for the nuclease and reverse transcriptase, and the other invokes a multimeric enzyme with each protomer containing a single active site capable of mediating both cleavage and extension.